2015
DOI: 10.1371/journal.pone.0140499
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Gene and Protein Expression by Zinc Oxide Nanoparticles in Hen’s Ovarian Granulosa Cells: Specific Roles of Nanoparticles

Abstract: Annually, tons and tons of zinc oxide nanoparticles (ZnO NPs) are produced in the world. And they are applied in almost all aspects of our life. Their release from the products into environment may pose issue for human health. Although many studies have reported the adverse effects of ZnO NPs on organisms, little is known about the effects on female reproductive systems or the related mechanisms. Quantitative proteomics have not been applied although quantitative transcriptomics have been used in zinc oxide na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…Omics-based approaches such as transcriptomics have been applied extensively for profiling gene expression changes upon ENM exposure [25,2730]. Although these studies provide valuable information on how ENMs alter gene expression, the changes at the mRNA level do not necessarily correlate with changes at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…Omics-based approaches such as transcriptomics have been applied extensively for profiling gene expression changes upon ENM exposure [25,2730]. Although these studies provide valuable information on how ENMs alter gene expression, the changes at the mRNA level do not necessarily correlate with changes at the protein level.…”
Section: Introductionmentioning
confidence: 99%
“…They are heavily used due to their unique characteristics, such as high hydrophilicity, and ease of synthesis [ 21 , 22 ]. The increasing use of nanomaterials has raised concerns about the potential risks to human health, especially on the reproduction system [ 5 , 23 , 24 ]. Several studies have addressed the concerns of NPs exposure on reproductive health, however these studies focused on the impact of NPs on germ cell and pregnancy complications [ 5 , 20 , 25 ] ( Figure 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…The methods for characterization of ZnO NPs were just published in our previous paper [ 41 ]. ZnO NPs were synthesized by Beijing DK nano technology Co. LTD (Beijing, P. R. China).…”
Section: Methodsmentioning
confidence: 99%
“…By reinforcing transcriptional programs and attenuating aberrant transcripts, microRNAs help to confer robustness to biological processes [ 40 ]. ZnO NPs have been reported to result in adverse effect on organisms and to change the expression of genes related to cytoskeletal transport, cellular respiration, and reproduction in Daphnia magna [ 16 ], and in our recent study we found ZnO NPs regulate the protein expression too [ 41 ]. Do microRNAs buffer against the variation in gene expression caused by ZnO NPs?…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation